2005
DOI: 10.1093/schbul/sbj021
|View full text |Cite
|
Sign up to set email alerts
|

Data Gathering: Biased in Psychosis?

Abstract: This study examined whether the probabilistic reasoning bias referred to as a "jumping-to-conclusions" (JTC) style of reasoning, which, according to previous research, is associated with particular psychotic symptoms such as delusions, represents a trait that can also be detected in nonpsychotic relatives of patients with schizophrenia and in nonpsychotic individuals with a high level of psychotic experiences. Participants were, in order of level of psychosis liability, 40 patients with schizophrenia or a schi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
149
1
5

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 183 publications
(169 citation statements)
references
References 87 publications
13
149
1
5
Order By: Relevance
“…In support of this, Menon et al [2 ] found that antipsychotic treatment in patients with schizophrenia did not reduce the bias which may suggest that jumping to conclusions bias could be a trait maker for schizophrenia. This bias has also been observed in irst-degree relatives of patients with schizophrenia above all patients with delusions [26]. Similarly, these cognitive biases have been observed in patients with psychosis.…”
Section: Jumping To Conclusion Against Disconirmatory Evidencesupporting
confidence: 61%
See 1 more Smart Citation
“…In support of this, Menon et al [2 ] found that antipsychotic treatment in patients with schizophrenia did not reduce the bias which may suggest that jumping to conclusions bias could be a trait maker for schizophrenia. This bias has also been observed in irst-degree relatives of patients with schizophrenia above all patients with delusions [26]. Similarly, these cognitive biases have been observed in patients with psychosis.…”
Section: Jumping To Conclusion Against Disconirmatory Evidencesupporting
confidence: 61%
“…In fact, most studies have found this bias in patients with schizophrenia who have positive symptoms and not in patients with schizophrenia who have a negative symptomatology. Therefore, this bias is more associated with the delusions rather than with schizophrenia disorder [26]. The JTC is found in people with delusions with a schizophrenia diagnosis or delusional disorder.…”
Section: Jumping To Conclusion Against Disconirmatory Evidencementioning
confidence: 92%
“…That is, they tend to draw conclusions based on less evidence than nondelusional participants (e.g., Huq et al, 1988;Garety et al, 1991;Garety et al, 2005;van Dael et al, 2006;Langdon et al, 2010; for a review see Fine et al, 2007). Even though the conclusions reached in the typical jump to conclusions paradigm are not of delusional content, such a mechanism of hasty decision-making can help explain why someone could consider a false belief in the first place (Ziegler et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Both clinical and non clinical psychosis are associated with (i) demographical risk factors such as younger age (a peak of symptoms in adolescence and a decrease after young adulthood) (Verdoux et al, 1998), being single or unemployed ) and gender, with women reporting more positive symptoms and men more negative symptoms ; and (ii) (environmental) risk factors such as urbanicity, trauma, cannabis, neuroticism (Myin Germeys, van Os, Krabbendam, Myin Germeys, & Delespaul, 2005). Finally, familial clustering is evident in regard to both symptomatology (Fanous, Gardner, Walsh & Kendler, 2001) and underlying cognitive (Barkus, Stirling, Hopkins, & Lewis, 2006;van Dael et al, 2005;Jabben, van Os, Janssen, Versmissen, & Krabbendam, 2007;Vollema & Postma, 2002) and psychophysiological mechanisms. For example, relatives of patients with schizophrenia…”
Section: The Extended Psychosis Phenotypementioning
confidence: 99%
“…An increasingly influential paradigm for the study of psychosis is a dimensional one, in which psychosis is no longer seen as an all or nothing phenomenon, but rather as a continuum of severity, ranging from normal functioning on the one end through eccentricity and subclinical psychotic symptoms to clinical prodromes and florid psychosis on the other extreme end (van Dael et al, 2005). This shift from studying broad, heterogeneous and categorical concepts such as schizophrenia towards studying an extended psychosis phenotype that encompasses all cross diagnostic psychotic phenomena, clinical and subclinical, seems a promising approach.…”
Section: Goalsmentioning
confidence: 99%